ANALISIS PENGGUNAAN INSTAGRAM SEBAGAI MEDIA PROMOSI TERHADAP MINAT MENGINAP DI HOTEL RENAISSANCE BALI ULUWATU RESORT & SPA - Sari Dewi, Ni Komang Novita; Sarjana, I Made; Artatanaya, I Gusti Lanang Suta; Sri Widhari, Cokorda Istri (Jurnal Ilmiah Tata Sejuta STIA Mataram, 2023)
This study aims to determine the effect of Context, Communication, Collaboration, Connection on interest in staying at the Renaissance Bali Uluwatu Resort & Spa Hotel. In this study, the type of data used is Quantitative Data. In this study, the reseach population is all followers of Instagram social media belonging to Hotel Renaissance Bali Uluwatu Resort & Spa named @renhotelbali and using a sample of 100 respondents. The distribution of the questionnaire in this study was carried out online via a google form link to respondents who are followers of Instagram @renhotelbali by sending a questionnaire link via Direct Messages (DM). Data analysis was carried out with several tests which included instrument tests in the form of validity and reliability tests, classical assumption tests in the form of normality tests, multicollinearity tests, and heteroscedasticity tests, multiple linear regression analysis tests and hypothesis tests including t tests, f tests and the coefficient of determination. In the partial hypothesis testing, it shows that Context and Collaboration have a positive and significant influence on interest in staying, while Communication and Connection partially does not have a positive and significant influence on interest in staying at the Renaissance Bali Hotel Uluwatu Resort & Spa. However, with the simultaneous test Context, Communication, Collaboration, Connection has an influence on interest in staying.